Regional Policy Forum: Opportunities for a Climate-Smart Food System in the Philippines - Baruah, Sampriti (2019)
The International Potato Center (CIP) in collaboration with Climate Change, Agriculture and Food Security (CCAFS) organized a Regional Policy Forum on “Opportunities for a climate-smart food system in the Philippines” on February 7, 2019 at Astoria Plaza, Ortigas Business District, Pasig City, Philippines. A total of 63 participants from the government, policy institutes, international organizations, academia and the civil society participated.